Observations from structural testing of full-scale tidal turbine blades (Proceedings of the European Wave and Tidal Energy Conference, 2023)
As the world shifts its reliance from fossil fuels to renewable energy, a reliable, predictable and dependable source of energy is vital; tidal energy provides such a solution. In 2021, the cumulative installed capacity of tidal stream energy in Europe, since 2010, reached 30.2 MW, which is roughly three times as much as the rest of the world. The total electricity produced in Europe from tidal energy increased by 8 GWh to a total of 68 GWh to date. The tidal turbine blades convert the energy in the tidal current to useful mechanical energy that can be converted to electricity. Therefore, the reliability of the blades is paramount to the success for the turbine. Structural testing of composite tidal turbine blades is performed to ensure the design and manufacturing processes [4] produce a reliable component that performs for its design life span. In recent years, a number of structural testing programmes have been performed on full-scale tidal turbine blades, as the sector strives for commercial viability.In this paper, observations during the structural (static, dynamic and fatigue) testing of full-scale tidal turbine blades are presented and discussed. These observations have been made from 5 testing campaigns on full-scale tidal turbine blades at the Large Structures Testing Laboratory in the SFI MaREI centre in the University of Galway. The length of these blades range from 2-8 metres, for devices of 70kW to 2MW. Therefore, primary aim of this paper is to report significant observations from the full-scale structural testing of tidal turbine blades. The experience gained from these structural testing programmes highlighted a number of best practices that could be introduced to the next revision of both the IEC 62600-3:2020 test specification and the DNV-ST-0164 standard, which includes using a combined flapwise-edgewise loading, the use of a multi-actuator load introduction system to ensure a correct load distribution and the duration of the holding time for static testing.The inclusion of these potential best practices could benefit all of the tidal energy sector by being included in the next version of the relevant testing standards. These activities, along with the successful testing programmes that has allowed the developers to deploy their devices for operational trials, helps de-risk tidal energy technology aiding in lowering the levelised cost of tidal energy.